(untitled) (Academicia Globe: Inderscience Research, 2022)
We studied the respiratory viruses which are unique to the lungs with their characteristics and description, which include various types such as H5N1 influenza A, influenza viruses, human metapneumovirus (HMPV), parainfluenza viruses, adenoviruses, human respiratory syncytial virus (HRSV), and picornaviruses. Also, the most widespread virus that infects the respiratory system, Coronaviruses, were discussed, with emphasis on their epidemiology, pathogenicity, clinical features, and diagnosis approaches. There are several approaches and strategies to detect respiratory viruses, which are discussed in this work. Furthermore, the importance of immunity against viral respiratory infections, which are initiated via the innate immune system and followed by adaptive immunological responses, was emphasized.